A CuZr shape memory amorphous composite material and preparation method thereof

Through the synergistic influence of vacuum electron beam micro-zone remelting technology and microalloyization, the problems of brittle fracture and processing softening of CuZr shape memory alloy at room temperature were solved, and amorphous composite materials with high strength and high toughness sandwich structure were prepared, realizing industrial applications with controllable structure and good repeatability of the material.

CN118241057BActive Publication Date: 2025-04-04SHANDONG UNIV SHENZHEN RES INST +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410261651.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-07
Publication Date
2025-04-04
Estimated Expiration
2044-03-07

AI Technical Summary

Technical Problem

CuZr shape memory alloy exhibits brittle fracture and processing softening problems at room temperature, and the preparation of amorphous composite materials with sandwich structure is difficult, which affects its industrial application.

Method used

The vacuum electron beam micro-region remelting technology and microalloyization synergistically affect the glass formation ability and mechanical properties of amorphous alloys. By introducing microalloy elements with positive mixing enthalpy, the amorphous formation ability and mechanical properties of CuZr shape memory alloys are improved, and the spatial distribution, particle size and volume fraction of the shape memory B2 CuZr phase is achieved.

Benefits of technology

A metal amorphous composite material with controllable structure and good repeatability is prepared, which solves the problem of rapid reduction of amorphous content under high temperature and high pressure conditions, improves the stability and reliability of product research and development, and promotes industrialization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118241057B_ABST
    Figure CN118241057B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of metallic amorphous alloy materials, and discloses a CuZr shape memory type amorphous composite material and a preparation method thereof. The CuZr shape memory type amorphous composite material is based on a Cu x Zr y Al z alloy as the matrix, and is prepared by introducing a doping element X. The chemical general formula of the CuZr shape memory type amorphous composite material is (Cu x Zr y Al z ) 100‑n M n ; the structure of the CuZr shape memory type amorphous composite material is a sandwich structure, and from top to bottom, it is successively a surface layer, an intermediate layer, and a matrix layer; wherein, M is one or both of Fe and Ta; n is the atomic percentage content of X, and 0% < n% ≤ 2%; x, y, and z are respectively the atomic percentage contents of Cu, Zr, and Al in the Cu x Zr y Al z alloy, and 44% ≤ x% ≤ 48%, 44% ≤ y% ≤ 48%, 6% ≤ z% ≤ 8%, and x + y + z = 100. The CuZr shape memory type amorphous composite material of the present invention has excellent mechanical properties, broadens the application prospects of amorphous composite materials, and has good industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal amorphous alloy materials, and in particular to a CuZr shape memory amorphous composite material and a preparation method thereof. Background Art

[0002] CuZr shape memory alloy has become a research hotspot in the fields of aerospace, precision machinery and biomedicine due to its unique shape memory effect and excellent mechanical properties.

[0003] However, CuZr shape memory alloys exhibit brittle fracture and processing softening problems at room temperature, which limits the scope of their industrial applications. In order to solve the above technical problems, researchers in this field have proposed to improve the room temperature plasticity and toughness of CuZr amorphous alloys by introducing shape memory B2 CuZr phases. Although the elemental composition and glass forming ability of amorphous alloys can be regulated by microalloying and optimizing preparation conditions, thereby affecting the precipitation of B2 CuZr phases, it is still a technical challenge to control parameters such as the spatial distribution, particle size and volume fraction of these second phases. In addition, the preparation of sandwich-structured amorphous composites is more difficult. Sandwich-structured composite materials are composed of two outer layers of material and an intermediate core layer. Although this structure can effectively improve the strength and stiffness of the material while maintaining lightweight, the amorphous alloy has a small formation size and weak formation ability. In addition, the amorphous phase is easily degraded under high temperature and high pressure conditions. These problems have seriously limited the preparation and application of sandwich-structured amorphous composites.

[0004] To this end, the present invention provides a CuZr shape memory amorphous composite material and a preparation method thereof. Summary of the invention

[0005] In order to solve the deficiencies in the above-mentioned prior art, the present invention provides a CuZr shape memory amorphous composite material and a preparation method thereof. The present invention aims to reduce the rapid reduction of amorphous content under high temperature and high pressure conditions, and adopts vacuum electron beam micro-area remelting technology to ensure that while maintaining the unique properties of amorphous alloys, it can also meet the rapid development needs of industrial applications. At the same time, the present invention also analyzes the reasons why CuZr shape memory alloys exhibit brittle fracture and processing softening at room temperature, and finds that it is mainly due to the highly localized shear band formation mechanism of amorphous alloys, which causes CuZr shape memory alloys to easily produce brittle fractures without warning when subjected to stress. Therefore, the present invention takes mixing enthalpy as the research basis, increases the micro-alloying elements of positive mixing enthalpy to improve the amorphous forming ability and mechanical properties of CuZr shape memory alloys, so as to achieve precise control of the spatial distribution, particle size and volume fraction of the shape memory B2 CuZr phase, thereby preparing a metal amorphous composite material with a controllable structure and good repeatability, high strength, and high toughness sandwich structure. The preparation method of the present invention has unique advantages, can effectively solve the above problems, improve the stability and reliability of product research and development, is conducive to the rapid advancement of industrialization, and provides a new path for the industrial application of CuZr shape memory alloys and their amorphous composite materials.

[0006] The CuZr shape memory amorphous composite material and the preparation method thereof of the present invention are realized by the following technical scheme:

[0007] The first object of the present invention is to provide a method for preparing a CuZr shape memory amorphous composite material. The present invention prepares an amorphous alloy plate under the premise of synergistically affecting the glass forming ability and mechanical properties of the amorphous alloy itself through microalloying, and then performs vacuum electron beam surface remelting on the surface of the obtained amorphous alloy plate. By performing vacuum electron beam micro-area remelting on the surface of an existing bulk amorphous plate, a high-strength and high-toughness metal sandwich structure amorphous composite material with adjustable microstructure and performance can be obtained by controlling different melting currents or scanning speeds. The CuZr shape memory amorphous composite material of the present invention is referred to as (Cu x Zr y Al z ) 100-n M n For example, through (Cu x Zr y Al z ) 100-n M n The specific technical solution of the present invention is described. For example, when it is necessary to prepare a Cu-based x Zr y Al z When the CuZr shape memory amorphous composite material is prepared by using Cu xZr y Al z The alloy is used as the matrix and is prepared by introducing a doping element M. The chemical general formula of the CuZr shape memory amorphous composite material is (Cu x Zr y Al z ), and the specific preparation method includes the following steps: 100-n M n , and specifically the preparation method includes the following steps:

[0008] Step 1: According to the stoichiometric relationship of the alloy material (Cu x Zr y Al z ), weigh out the corresponding masses of each metal single-element raw material and set aside. 100-n M n , respectively weigh out the corresponding masses of each metal single-element raw material and set aside.

[0009] Among them, M is one or both of Fe and Ta.

[0010] n is the atomic percentage content of the doping element M in the CuZr shape memory amorphous composite material, and 0% ≤ n% ≤ 2%.

[0011] x, y, and z are the atomic percentage contents of Cu, Zr, and Al in the Cu x Zr y Al z alloy, and 44% ≤ x% ≤ 48%, 44% ≤ y% ≤ 48%, 6% ≤ z% ≤ 8%, and x + y + z = 100.

[0012] It should be noted that the above 0% ≤ n% ≤ 2% includes two cases where n is 0 and n is not 0, that is, the two cases of not introducing the doping element M and introducing the doping element M: when n is 0, that is, not introducing the doping element M, that is, weighing out the corresponding masses of pure copper, pure zirconium, and pure aluminum according to the stoichiometric relationship of Cu x Zr y Al z ; when n is not 0, that is, 0% < n% ≤ 2%, introducing the doping element M, that is, weighing out the corresponding masses of pure copper, pure zirconium, pure aluminum, and pure M according to the stoichiometric relationship of Cu x Zr y Al z .

[0013] In either of the above cases, the present invention uses the massive pure metal simple substances corresponding to each element as the preparation raw materials and reserves them. In a preferred embodiment of the present invention, in order to avoid introducing other unnecessary impurities, the purity of pure copper, pure zirconium, pure aluminum, and pure M is all ≥99.99%. And in order to avoid the possible oxide layer on the surface of the massive pure metal simple substances, before weighing, the surfaces of the respective massive pure metal simple substances are first polished to remove the oxide skin, and each raw material is ultrasonically cleaned with an acetone / water cleaning solution.

[0014] Step 2: Place the weighed metal simple substance raw materials in an electric arc furnace, evacuate and then fill with argon, and perform at least 3 times of electric arc melting treatment under argon to obtain an alloy ingot.

[0015] It should be noted that when n is 0, that is, pure copper, pure zirconium, and pure aluminum are placed in the electric arc furnace in descending order of melting point from top to bottom. When 0% < n% ≤ 2%, when pure copper, pure zirconium, pure aluminum, and pure M are placed, they are placed in descending order of melting point from top to bottom.

[0016] Taking into account the factor of melting point, in a preferred embodiment of the present invention, after the placement is completed, the electric arc furnace is evacuated, and the evacuation is carried out to a vacuum degree ≤ 3.0×10 -4 Pa to reduce the influence of impurity gases during the melting process.

[0017] Taking into account the factors of impurity gases such as oxygen and carbon dioxide, in a preferred embodiment of the present invention, when filling with argon, it is filled to a pressure of 0.6 - 0.8 atmospheres to prevent oxidation and contamination.

[0018] In order to ensure that each preparation raw material is fully mixed, the present invention performs at least 3 times of electric arc melting treatment. And in a preferred embodiment of the present invention, during each electric arc melting treatment, the melting current is 300 - 400 A, the melting time is 60 - 90 s, and the interval time between two adjacent electric arc melting treatments is 2 - 3 min.

[0019] Step 3: Melt the alloy ingot to form a molten liquid, place the molten liquid in a mold, and after cooling, obtain an amorphous alloy sheet.

[0020] It should be noted that in order to melt the alloy ingot to form a molten liquid, in a preferred embodiment of the present invention, the alloy ingot is cut into pieces and placed in a suction casting copper mold, melted under the conditions of vacuum arc melting to obtain a molten liquid, and then sucked into a water-cooled copper mold by vacuum suction casting method. At 5×10 4K / s cooling rate, and then rapidly solidified to obtain an amorphous alloy sheet. In addition, the present invention adopts a water-cooled copper mold for cooling. Since the cooling rate of the upper part of the water-cooled copper mold is lower than the cooling rate of the lower part of the mold, the solidification process and the final microstructure of the material are effectively controlled to achieve the purpose of optimizing the material performance.

[0021] Step 4: placing the amorphous alloy plate on a substrate, and performing vacuum electron beam micro-area remelting treatment on the surface of the amorphous alloy plate to sequentially form an ultra-thin surface melting layer and a heat-affected layer on the surface of the amorphous alloy plate to obtain an amorphous material with a sandwich structure, namely, the CuZr shape memory amorphous composite material.

[0022] It should be noted that the vacuum electron beam micro-area remelting technology used in the present invention can prepare large-scale, industrial-grade sandwich amorphous composite structure materials without destroying the amorphous forming ability, so that it can simultaneously have the characteristics of high strength of amorphous alloys and high plasticity of crystal structures, forming a high-strength and high-toughness sandwich composite structure. Compared with laser remelting technology, the electron beam has lower reflectivity, greater energy input, and smaller melting keyholes, which can make the heat-affected zone of amorphous alloys smaller during heating, and the sandwich amorphous composite structure is easier to control.

[0023] It should be noted that when the energy input of the electron beam is too low, the amorphous alloy plate cannot form a sandwich structure; and when the energy input of the electron beam is too high, the sandwich structure of the amorphous alloy plate will be too thick, thereby affecting its shape memory performance. When the beam current of the electron beam is constant, increasing the scanning speed will reduce the energy input per unit area; when the scanning speed is constant, increasing the beam current of the electron beam will increase the energy input per unit area. Therefore, the present invention can effectively regulate the organizational structure distribution of the amorphous composite material by regulating the beam current and scanning speed of the electron beam, thereby regulating the performance of the amorphous composite material to meet the requirements of different use environments. In a preferred embodiment of the present invention, the process parameters of the vacuum electron beam micro-area remelting treatment are: the vacuum degree of the furnace chamber is ≤8×10 -3 Pa, the vacuum degree of the welding chamber is ≤9×10 -3 Pa; the focusing current of the electron beam is 607-608 mA, the scanning frequency is 500 Hz, the bias voltage is 1800 V, the filament current is 18 A, and the high voltage used is 70 kV; under the condition that the vacuum electron beam scanning mode is the surface scanning mode, the spot diameter is 200 μm, the scanning speed is 500-1200 mm / min, and the beam current of the electron beam is 1-8 mA. In another preferred embodiment of the present invention, the scanning speed is 800-1000 mm / min, and the beam current of the electron beam is 5-7 mA.

[0024] The second object of the present invention is to provide a CuZr shape memory amorphous composite material obtained by the above preparation method. It should be noted that the above 0%≤n%≤2% includes two cases where n is 0 and n is not 0, that is, two cases where the doping element M is not introduced and where the doping element M is introduced.

[0025] When the doping element M is not introduced, that is, the CuZr shape memory amorphous composite material of the present invention is Cu x Zr y Al z Alloy, and it should be particularly emphasized that the CuZr shape memory amorphous composite material Cu x Zr y Al z The structure of the alloy is a sandwich structure, and from top to bottom, it is an upper surface layer, an intermediate layer, and a lower surface layer. The upper surface layer includes an upper surface ultra-thin zone and an upper heat-affected zone from top to bottom, and the upper surface ultra-thin zone is an amorphous structure; the upper heat-affected zone is located between the surface ultra-thin zone and the intermediate layer, and the upper heat-affected zone is a shape memory type B2 crystal phase. The lower surface layer includes a lower heat-affected zone and a lower surface ultra-thin zone from top to bottom, and the lower heat-affected zone is located between the surface ultra-thin zone and the intermediate layer, and the upper heat-affected zone is a shape memory type B2 crystal phase; the lower surface ultra-thin zone is an amorphous structure.

[0026] It should be emphasized that when the doping element M is introduced, the CuZr shape memory amorphous composite material (Cu x Zr y Al z ) 100-n M n It also has a sandwich structure, and from top to bottom it is an upper surface layer, an intermediate layer, and a lower surface layer. And (Cu x Zr y Al z ) 100-n M n In the above Cu x Zr y Al z The mechanical properties of CuZr shape memory amorphous composites (Cu x Zr y Al z ) 100-n M n It can be regarded as Cu x Zr y Al z Alloy is used as the matrix, and Fe and / or Ta are used as doping elements to achieve Cu x Zry Al z The cast mechanical properties of the alloy are improved, and amorphous composite materials with different performance improvement effects are obtained according to the different doping elements introduced. Among them, when the Fe element is introduced alone, the amorphous composite material obtained has a large positive mixing heat with Fe and Cu, while Fe, Zr and Al have a large negative mixing heat. In this case, due to the energy advantage, phase separation may occur, forming a heterogeneous structure, resulting in enhanced plasticity. When the Ta element is introduced alone, the partial substitution of Ta for Zr in the amorphous composite material obtained will lead to the formation of a non-uniform structure, which can form strong medium- and short-range ordered clusters in the amorphous phase, thereby improving the Cu x Zr y Al z Plasticity of the alloy. When Fe and Ta are introduced simultaneously, the amorphous composite material obtained is a high-entropy alloy-like material with the special properties of high-entropy alloys, which makes the prepared alloy material have high configuration entropy, high amorphous forming ability and thermal stability. In addition, the simultaneous addition of Fe and Ta can affect the expansion of the shear band, thereby improving the plasticity of the alloy material.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The present invention takes into account that the amorphous content of the amorphous composite material will decrease rapidly under high temperature and high pressure conditions. Therefore, after melting and casting each raw material to form an amorphous alloy plate, the present invention adopts a vacuum electron beam micro-area remelting technology to form a heat-affected layer and a surface ultra-thin melting layer on the upper and lower surfaces of the amorphous alloy plate, and prepares a large-scale, industrial-grade sandwich amorphous composite structure material without destroying the amorphous forming ability, so that it can simultaneously have the characteristics of high strength of amorphous alloy and high plasticity of crystal structure, forming a high-strength and high-toughness sandwich composite structure, thereby avoiding the defect that the amorphous content of the amorphous composite material will decrease rapidly under high temperature and high pressure conditions. And the present invention can achieve effective regulation of the organizational structure distribution of the amorphous composite material by regulating the beam size and scanning speed of the electron beam, and then achieve regulation of the performance of the amorphous composite material, so that it can meet the requirements of different use environments.

[0029] The present invention analyzes the reasons why the CuZr shape memory alloy exhibits brittle fracture and processing softening at room temperature, and finds that it is mainly due to the highly localized shear band formation mechanism of the amorphous alloy, which causes the CuZr shape memory alloy to easily produce brittle fracture without warning when subjected to stress. Therefore, the present invention takes mixing enthalpy as the research basis, and introduces a microalloying element M with positive mixing enthalpy on the basis of the original CuZr shape memory alloy components to improve the amorphous forming ability and mechanical properties of the CuZr shape memory alloy, so as to achieve precise control of the spatial distribution, particle size and volume fraction of the shape memory B2 CuZr phase, thereby preparing a metal amorphous composite material with a controllable structure and good repeatability, a high-strength and high-toughness sandwich structure. The present invention uses Fe and / or Ta as doping elements to achieve the control of Cu by doping elements. x Zr y Al z The cast mechanical properties of the alloy are improved, and amorphous composite materials with different performance improvement effects are obtained according to the different doping elements introduced. Among them, when the Fe element is introduced alone, the amorphous composite material obtained has a large positive mixing heat with Fe and Cu, while Fe, Zr and Al have a large negative mixing heat. In this case, due to the energy advantage, phase separation may occur, forming a heterogeneous structure, resulting in enhanced plasticity. When the Ta element is introduced alone, the partial substitution of Ta for Zr in the amorphous composite material obtained will lead to the formation of a non-uniform structure, which can form strong medium- and short-range ordered clusters in the amorphous phase, thereby improving the Cu x Zr y Al z Plasticity of the alloy. When Fe and Ta are introduced simultaneously, the amorphous composite material obtained is a high-entropy alloy-like material with the special properties of high-entropy alloys, which makes the prepared alloy material have high configuration entropy, high amorphous forming ability and thermal stability. In addition, the simultaneous addition of Fe and Ta can affect the expansion of the shear band, thereby improving the plasticity of the alloy material.

[0030] The present invention introduces doping elements into the raw materials for preparing amorphous alloys, so as to synergistically affect the glass-forming ability and mechanical properties of the amorphous alloy itself through microalloying of the doping elements, thereby achieving improvement of the cast mechanical properties of the amorphous alloy. In addition, on the basis of the amorphous alloy sheet obtained after the introduction of the doping elements, the surface is subjected to vacuum electron beam surface remelting, which can form an amorphous state in the amorphous alloy sheet within a wide temperature range, and further improve the mechanical properties of the amorphous alloy on the basis of ensuring the amorphous content. The present invention can effectively improve the strength and stiffness of the amorphous composite material by combining the microalloying of the doping elements with the vacuum electron beam surface remelting technology, while maintaining its lightweight and giving full play to its high specific strength advantage, so as to achieve the goal of lightweighting aerospace, ships, warships and vehicle equipment.

[0031] The process method of the present invention is simple, which makes the organization and performance of the amorphous composite material more flexible, and can prepare large-sized samples, greatly broadening the application scope of the alloy field. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is the Cu of Example 1 46 Zr 46 Microstructure image of Al8 as-cast sample.

[0033] Figure 2 The microstructure pictures of the alloy samples of Example 2, Example 5, Example 6 and Example 7 are shown in FIG. Figure 2 (a) Figure 2 (b) Figure 2 (c) and Figure 2 (d) are microstructure images of the alloy samples of Example 2, Example 5, Example 6 and Example 7 at a scale of 200 μm.

[0034] Figure 3 This is a cross-sectional microscope image of the cast sample of Example 8.

[0035] Figure 4 For Comparative Example 2 (Cu 46 Zr 46 Al8) 98 Microstructure image of Fe1Ta1 as-cast sample.

[0036] Figure 5 The Cu of Comparative Example 3 46 Zr 46 Microstructure image of Al8 as-cast sample.

[0037] Figure 6 The graphs are the changes in the compressive mechanical properties of the cast samples of Comparative Examples 1-3 and Examples 1-8; wherein, Figure 6 (a) is a graph showing the changes in the compressive mechanical properties of Comparative Example 1 and Comparative Example 2. Figure 6 (b) is a graph showing the changes in the compressive mechanical properties of Comparative Example 3 and Examples 1-4, Figure 6 (c) is a graph showing changes in the compressive mechanical properties of Example 2, Example 5, Example 6, Example 7 and Example 8. DETAILED DESCRIPTION

[0038] As described in the background technology, the present invention proposes an amorphous composite material with a high-strength and high-toughness metal sandwich structure with adjustable microstructure and performance, and prepares an amorphous alloy sheet under the premise of synergistically affecting the glass-forming ability and mechanical properties of the amorphous alloy itself by microalloying, and then performs vacuum electron beam surface remelting on the surface of the obtained amorphous alloy sheet, and controls different melting currents or scanning speeds to obtain an amorphous composite material with a high-strength and high-toughness metal sandwich structure with adjustable microstructure and performance. The technical scheme in the embodiment of the present invention will be described clearly and completely below.

[0039] Example 1

[0040] This embodiment provides a method for preparing a CuZr shape memory amorphous composite material, comprising the following steps:

[0041] Step 1, Ingredients:

[0042] The surfaces of pure copper, pure zirconium and pure aluminum are polished to remove the oxide layer, and each raw material is ultrasonically cleaned with acetone / water cleaning solution, and then dried and set aside;

[0043] According to Cu 46 Zr 46 The atomic ratio of Al8 is calculated and the corresponding masses of pure copper, pure zirconium and pure aluminum after the above treatment are weighed based on a total mass of 30g for later use.

[0044] Step 2, preparing alloy ingots:

[0045] Using the arc melting method, the pure copper, pure zirconium and pure aluminum weighed in step 1 were placed in a water-cooled crucible in the order of melting point from high to low in an arc furnace, and the vacuum was evacuated to 3.0×10 -4 After the pressure reaches 0.7 Pa, argon gas is filled in and the pressure reaches 0.7 atmospheres. Four arc melting treatments are performed under argon gas to obtain an alloy ingot.

[0046] The smelting current is 350A each time, and the smelting time is 80s each time.

[0047] Step 3, preparing alloy plate:

[0048] The alloy ingot obtained in step 2 was cut into blocks of 10 mm × 10 mm × 8 mm in size, placed in a suction casting copper mold, melted in an argon atmosphere, and the molten liquid was sucked into a water-cooled copper mold by vacuum suction casting. 4 K / s cooling rate, and rapid solidification was achieved to obtain an amorphous alloy plate with a size of 2mm×8mm×50mm.

[0049] Step 4: vacuum electron beam micro-area remelting treatment:

[0050] The amorphous alloy plate obtained in step 3 is placed on a copper substrate with a size of 500 mm × 500 mm × 500 mm, and the vacuum degree of the vacuum electron beam micro-area remelting furnace chamber is ≤ 8 × 10 -3 Pa, the vacuum degree of the welding chamber is ≤9×10 -3 Pa, and then, a vacuum electron beam micro-area remelting treatment is performed to sequentially form an ultra-thin surface melting layer and a heat-affected layer on the surface of the amorphous alloy plate to obtain an amorphous material with a sandwich structure, namely, the CuZr shape memory amorphous composite material.

[0051] Among them, the focusing current of the electron beam is 607.4mA, the scanning frequency is 500Hz, the bias voltage is 1800V, the filament current is 18A, and the high voltage used is 70kV; the vacuum electron beam scanning mode is under the surface scanning mode, the spot diameter is 200μm, the scanning speed is 1000mm / min, and the electron beam current is 5mA.

[0052] Example 2

[0053] This embodiment provides a method for preparing a CuZr shape memory amorphous composite material, comprising the following steps:

[0054] Step 1, Ingredients:

[0055] The surfaces of pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum are polished to remove the oxide layer, and each raw material is ultrasonically cleaned with acetone / water cleaning solution, and then dried and set aside;

[0056] According to (Cu 46 Zr 46 Al8) 98 The atomic ratio of Fe1Ta1 is calculated and the corresponding masses of pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum after the above treatment are weighed based on a total mass of 30g for use.

[0057] Step 2, preparing alloy ingots:

[0058] Using the arc melting method, the pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum weighed in step 1 were placed in a water-cooled crucible in the order of melting point from high to low in an arc furnace, and the vacuum was evacuated to 3.0×10 -4 After the pressure reaches 0.7 Pa, argon gas is filled in and the pressure reaches 0.7 atmospheres. Four arc melting treatments are performed under argon gas to obtain an alloy ingot.

[0059] The smelting current is 350A each time, and the smelting time is 80s each time.

[0060] Step 3, preparing alloy plate:

[0061] The alloy ingot obtained in step 2 was cut into blocks of 10 mm × 10 mm × 8 mm in size, placed in a suction casting copper mold, melted in an argon atmosphere, and the molten liquid was sucked into a water-cooled copper mold by vacuum suction casting. 4 K / s cooling rate, and rapid solidification was achieved to obtain an amorphous alloy plate with a size of 2mm×8mm×50mm.

[0062] Step 4: vacuum electron beam micro-area remelting treatment:

[0063] The amorphous alloy plate obtained in step 3 is placed on a copper substrate with a size of 500 mm × 500 mm × 500 mm, and the vacuum degree of the vacuum electron beam micro-area remelting furnace chamber is ≤ 8 × 10 -3 Pa, the vacuum degree of the welding chamber is ≤9×10 -3 Pa, and then, a vacuum electron beam micro-area remelting treatment is performed to sequentially form an ultra-thin surface melting layer and a heat-affected layer on the surface of the amorphous alloy plate to obtain an amorphous material with a sandwich structure, namely, the CuZr shape memory amorphous composite material.

[0064] Among them, the focusing current of the electron beam is 607.4mA, the scanning frequency is 500Hz, the bias voltage is 1800V, the filament current is 18A, and the high voltage used is 70kV; the vacuum electron beam scanning mode is under the surface scanning mode, the spot diameter is 200μm, the scanning speed is 1000mm / min, and the electron beam current is 5mA.

[0065] That is, the only difference between this embodiment and embodiment 1 is that in this embodiment, pure iron and pure tantalum are also introduced at the same time.

[0066] Example 3

[0067] This embodiment provides a method for preparing a CuZr shape memory amorphous composite material, comprising the following steps:

[0068] Step 1, Ingredients:

[0069] The surfaces of pure copper, pure zirconium, pure aluminum and pure iron are polished to remove the oxide layer, and each raw material is ultrasonically cleaned with acetone / water cleaning solution, and then dried and set aside;

[0070] According to (Cu 46 Zr 46 Al8) 98 The atomic ratio of Fe2 is calculated and the corresponding masses of pure copper, pure zirconium, pure aluminum and pure iron after the above treatment are weighed based on the total mass of 30g, and set aside.

[0071] Step 2, preparing alloy ingots:

[0072] Using the arc melting method, the pure copper, pure zirconium, pure aluminum, and pure iron weighed in step 1 were placed in a water-cooled crucible in the order of melting point from high to low in an arc furnace, and the crucible was evacuated to 3.0×10 -4 After the pressure reaches 0.7 Pa, argon gas is filled in and the pressure reaches 0.7 atmospheres. Four arc melting treatments are performed under argon gas to obtain an alloy ingot.

[0073] The smelting current is 350A each time, and the smelting time is 80s each time.

[0074] Step 3, preparing alloy plate:

[0075] The alloy ingot obtained in step 2 was cut into blocks of 10 mm × 10 mm × 8 mm in size, placed in a suction casting copper mold, melted in an argon atmosphere, and the molten liquid was sucked into a water-cooled copper mold by vacuum suction casting. 4 K / s cooling rate, and rapid solidification was achieved to obtain an amorphous alloy plate with a size of 2mm×8mm×50mm.

[0076] Step 4: vacuum electron beam micro-area remelting treatment:

[0077] The amorphous alloy plate obtained in step 3 is placed on a copper substrate with a size of 500 mm × 500 mm × 500 mm, and the vacuum degree of the vacuum electron beam micro-area remelting furnace chamber is ≤ 8 × 10 -3 Pa, the vacuum degree of the welding chamber is ≤9×10 -3 Pa, and then, a vacuum electron beam micro-area remelting treatment is performed to sequentially form an ultra-thin surface melting layer and a heat-affected layer on the surface of the amorphous alloy plate to obtain an amorphous material with a sandwich structure, namely, the CuZr shape memory amorphous composite material.

[0078] Among them, the focusing current of the electron beam is 607.4mA, the scanning frequency is 500Hz, the bias voltage is 1800V, the filament current is 18A, and the high voltage used is 70kV; the vacuum electron beam scanning mode is under the surface scanning mode, the spot diameter is 200μm, the scanning speed is 1000mm / min, and the electron beam current is 5mA.

[0079] That is, the only difference between this embodiment and embodiment 1 is that pure iron is also introduced in this embodiment.

[0080] Example 4

[0081] This embodiment provides a method for preparing a CuZr shape memory amorphous composite material, comprising the following steps:

[0082] Step 1, Ingredients:

[0083] The surfaces of pure copper, pure zirconium, pure aluminum, and pure tantalum are polished to remove the oxide layer, and each raw material is ultrasonically cleaned with acetone / water cleaning solution, and then dried and set aside;

[0084] According to (Cu 46 Zr 46 Al8) 98 The atomic ratio of Ta2 is calculated and the corresponding masses of pure copper, pure zirconium, pure aluminum, and pure tantalum after the above treatment are weighed respectively based on a total mass of 30g for use.

[0085] Step 2, preparing alloy ingots:

[0086] Using the arc melting method, the pure copper, pure zirconium, pure aluminum, and pure tantalum weighed in step 1 were placed in a water-cooled crucible in the order of melting point from high to low in an arc furnace, and the vacuum was evacuated to 3.0×10 -4 After the pressure reaches 0.7 Pa, argon gas is filled in and the pressure reaches 0.7 atmospheres. Four arc melting treatments are performed under argon gas to obtain an alloy ingot.

[0087] The smelting current is 350A each time, and the smelting time is 80s each time.

[0088] Step 3, preparing alloy plate:

[0089] The alloy ingot obtained in step 2 was cut into blocks of 10 mm × 10 mm × 8 mm in size, placed in a suction casting copper mold, melted in an argon atmosphere, and the molten liquid was sucked into a water-cooled copper mold by vacuum suction casting. 4 K / s cooling rate, and rapid solidification was achieved to obtain an amorphous alloy plate with a size of 2mm×8mm×50mm.

[0090] Step 4: vacuum electron beam micro-area remelting treatment:

[0091] The amorphous alloy plate obtained in step 3 is placed on a copper substrate with a size of 500 mm × 500 mm × 500 mm, and the vacuum degree of the vacuum electron beam micro-area remelting furnace chamber is ≤ 8 × 10 -3 Pa, the vacuum degree of the welding chamber is ≤9×10 -3 Pa, and then, a vacuum electron beam micro-area remelting treatment is performed to sequentially form an ultra-thin surface melting layer and a heat-affected layer on the surface of the amorphous alloy plate to obtain an amorphous material with a sandwich structure, namely, the CuZr shape memory amorphous composite material.

[0092] Among them, the focusing current of the electron beam is 607.4mA, the scanning frequency is 500Hz, the bias voltage is 1800V, the filament current is 18A, and the high voltage used is 70kV; the vacuum electron beam scanning mode is under the surface scanning mode, the spot diameter is 200μm, the scanning speed is 1000mm / min, and the electron beam current is 5mA.

[0093] That is, the only difference between this embodiment and embodiment 1 is that pure tantalum is also introduced in this embodiment.

[0094] Example 5

[0095] This embodiment provides a method for preparing a CuZr shape memory amorphous composite material, comprising the following steps:

[0096] Step 1, Ingredients:

[0097] The surfaces of pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum are polished to remove the oxide layer, and each raw material is ultrasonically cleaned with acetone / water cleaning solution, and then dried and set aside;

[0098] According to (Cu 46 Zr 46 Al8) 98 The atomic ratio of Fe1Ta1 is calculated and the corresponding masses of pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum after the above treatment are weighed based on a total mass of 30g for use.

[0099] Step 2, preparing alloy ingots:

[0100] Using the arc melting method, the pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum weighed in step 1 were placed in a water-cooled crucible in the order of melting point from high to low in an arc furnace, and the vacuum was evacuated to 3.0×10 -4 After the pressure reaches 0.7 Pa, argon gas is filled in and the pressure reaches 0.7 atmospheres. Four arc melting treatments are performed under argon gas to obtain an alloy ingot.

[0101] The smelting current is 350A each time, and the smelting time is 80s each time.

[0102] Step 3, preparing alloy plate:

[0103] The alloy ingot obtained in step 2 was cut into blocks of 10 mm × 10 mm × 8 mm in size, placed in a suction casting copper mold, melted in an argon atmosphere, and the molten liquid was sucked into a water-cooled copper mold by vacuum suction casting. 4 K / s cooling rate, and rapid solidification was achieved to obtain an amorphous alloy plate with a size of 2mm×8mm×50mm.

[0104] Step 4: vacuum electron beam micro-area remelting treatment:

[0105] The amorphous alloy plate obtained in step 3 is placed on a copper substrate with a size of 500 mm × 500 mm × 500 mm, and the vacuum degree of the vacuum electron beam micro-area remelting furnace chamber is ≤ 8 × 10 -3 Pa, the vacuum degree of the welding chamber is ≤9×10 -3 Pa, and then, a vacuum electron beam micro-area remelting treatment is performed to sequentially form an ultra-thin surface melting layer and a heat-affected layer on the surface of the amorphous alloy plate to obtain an amorphous material with a sandwich structure, namely, the CuZr shape memory amorphous composite material.

[0106] Among them, the focusing current of the electron beam is 607.4mA, the scanning frequency is 500Hz, the bias voltage is 1800V, the filament current is 18A, and the high voltage used is 70kV; the vacuum electron beam scanning mode is under the surface scanning mode, the spot diameter is 200μm, the scanning speed is 1000mm / min, and the electron beam current is 5.5mA.

[0107] That is, the difference between this embodiment and embodiment 1 is that: in this embodiment, pure iron and pure tantalum are introduced at the same time; in this embodiment, the beam current of the electron beam is different, which is 5.5 mA.

[0108] Example 6

[0109] This embodiment provides a method for preparing a CuZr shape memory amorphous composite material, comprising the following steps:

[0110] Step 1, Ingredients:

[0111] The surfaces of pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum are polished to remove the oxide layer, and each raw material is ultrasonically cleaned with acetone / water cleaning solution, and then dried and set aside;

[0112] According to (Cu 46 Zr 46 Al8) 98 The atomic ratio of Fe1Ta1 is calculated and the corresponding masses of pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum after the above treatment are weighed based on a total mass of 30g for use.

[0113] Step 2, preparing alloy ingots:

[0114] Using the arc melting method, the pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum weighed in step 1 were placed in a water-cooled crucible in the order of melting point from high to low in an arc furnace, and the vacuum was evacuated to 3.0×10 -4After the pressure reaches 0.7 Pa, argon gas is filled in and the pressure reaches 0.7 atmospheres. Four arc melting treatments are performed under argon gas to obtain an alloy ingot.

[0115] The smelting current is 350A each time, and the smelting time is 80s each time.

[0116] Step 3, preparing alloy plate:

[0117] The alloy ingot obtained in step 2 was cut into blocks of 10 mm × 10 mm × 8 mm in size, placed in a suction casting copper mold, melted in an argon atmosphere, and the molten liquid was sucked into a water-cooled copper mold by vacuum suction casting. 4 K / s cooling rate, and rapid solidification was achieved to obtain an amorphous alloy plate with a size of 2mm×8mm×50mm.

[0118] Step 4: vacuum electron beam micro-area remelting treatment:

[0119] The amorphous alloy plate obtained in step 3 is placed on a copper substrate with a size of 500 mm × 500 mm × 500 mm, and the vacuum degree of the vacuum electron beam micro-area remelting furnace chamber is ≤ 8 × 10 -3 Pa, the vacuum degree of the welding chamber is ≤9×10 -3 Pa, and then, a vacuum electron beam micro-area remelting treatment is performed to sequentially form an ultra-thin surface melting layer and a heat-affected layer on the surface of the amorphous alloy plate to obtain an amorphous material with a sandwich structure, namely, the CuZr shape memory amorphous composite material.

[0120] Among them, the focusing current of the electron beam is 607.4mA, the scanning frequency is 500Hz, the bias voltage is 1800V, the filament current is 18A, and the high voltage used is 70kV; the vacuum electron beam scanning mode is under the surface scanning mode, the spot diameter is 200μm, the scanning speed is 1000mm / min, and the electron beam current is 6mA.

[0121] That is, the difference between this embodiment and embodiment 1 is that: in this embodiment, pure iron and pure tantalum are introduced at the same time; and the beam current of the electron beam is also different, which is 6 mA.

[0122] Example 7

[0123] This embodiment provides a method for preparing a CuZr shape memory amorphous composite material, comprising the following steps:

[0124] Step 1, Ingredients:

[0125] The surfaces of pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum are polished to remove the oxide layer, and each raw material is ultrasonically cleaned with acetone / water cleaning solution, and then dried and set aside;

[0126] According to (Cu 46 Zr 46 Al8) 98 The atomic ratio of Fe1Ta1 is calculated and the corresponding masses of pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum after the above treatment are weighed based on a total mass of 30g for use.

[0127] Step 2, preparing alloy ingots:

[0128] Using the arc melting method, the pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum weighed in step 1 were placed in a water-cooled crucible in the order of melting point from high to low in an arc furnace, and the vacuum was evacuated to 3.0×10 -4 After the pressure reaches 0.7 Pa, argon gas is filled in and the pressure reaches 0.7 atmospheres. Four arc melting treatments are performed under argon gas to obtain an alloy ingot.

[0129] The smelting current is 350A each time, and the smelting time is 80s each time.

[0130] Step 3, preparing alloy plate:

[0131] The alloy ingot obtained in step 2 was cut into blocks of 10 mm × 10 mm × 8 mm in size, placed in a suction casting copper mold, melted in an argon atmosphere, and the molten liquid was sucked into a water-cooled copper mold by vacuum suction casting. 4 K / s cooling rate, and rapid solidification was achieved to obtain an amorphous alloy plate with a size of 2mm×8mm×50mm.

[0132] Step 4: vacuum electron beam micro-area remelting treatment:

[0133] The amorphous alloy plate obtained in step 3 is placed on a copper substrate with a size of 500 mm × 500 mm × 500 mm, and the vacuum degree of the vacuum electron beam micro-area remelting furnace chamber is ≤ 8 × 10 -3 Pa, the vacuum degree of the welding chamber is ≤9×10 -3 Pa, and then, a vacuum electron beam micro-area remelting treatment is performed to sequentially form an ultra-thin surface melting layer and a heat-affected layer on the surface of the amorphous alloy plate to obtain an amorphous material with a sandwich structure, namely, the CuZr shape memory amorphous composite material.

[0134] Among them, the focusing current of the electron beam is 607.4mA, the scanning frequency is 500Hz, the bias voltage is 1800V, the filament current is 18A, and the high voltage used is 70kV; the vacuum electron beam scanning mode is under the surface scanning mode, the spot diameter is 200μm, the scanning speed is 1000mm / min, and the electron beam current size is 7mA.

[0135] That is, the difference between this embodiment and embodiment 1 is that: in this embodiment, pure iron and pure tantalum are introduced at the same time; and the beam current of the electron beam is also different, which is 7 mA.

[0136] Example 8

[0137] Step 1, Ingredients:

[0138] The surfaces of pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum are polished to remove the oxide layer, and each raw material is ultrasonically cleaned with acetone / water cleaning solution, and then dried and set aside;

[0139] According to (Cu 46 Zr 46 Al8) 98 The atomic ratio of Fe1Ta1 is calculated and the corresponding masses of pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum after the above treatment are weighed based on a total mass of 30g for use.

[0140] Step 2, preparing alloy ingots:

[0141] Using the arc melting method, the pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum weighed in step 1 were placed in a water-cooled crucible in the order of melting point from high to low in an arc furnace, and the vacuum was evacuated to 3.0×10 -4 After the pressure reaches 0.7 Pa, argon gas is filled in and the pressure reaches 0.7 atmospheres. Four arc melting treatments are performed under argon gas to obtain an alloy ingot.

[0142] The smelting current is 350A each time, and the smelting time is 80s each time.

[0143] Step 3, preparing alloy plate:

[0144] The alloy ingot obtained in step 2 was cut into blocks of 10 mm × 10 mm × 8 mm in size, placed in a suction casting copper mold, melted in an argon atmosphere, and the molten liquid was sucked into a water-cooled copper mold by vacuum suction casting. 4 K / s cooling rate, and rapid solidification was achieved to obtain an amorphous alloy plate with a size of 2mm×8mm×50mm.

[0145] Step 4: vacuum electron beam micro-area remelting treatment:

[0146] The amorphous alloy plate obtained in step 3 is placed on a copper substrate with a size of 500 mm × 500 mm × 500 mm, and the vacuum degree of the vacuum electron beam micro-area remelting furnace chamber is ≤ 8 × 10 -3 Pa, the vacuum degree of the welding chamber is ≤9×10 -3Pa, and then, a vacuum electron beam micro-area remelting treatment is performed to sequentially form an ultra-thin surface melting layer and a heat-affected layer on the surface of the amorphous alloy plate to obtain an amorphous material with a sandwich structure, namely, the CuZr shape memory amorphous composite material.

[0147] Among them, the focusing current of the electron beam is 607.4mA, the scanning frequency is 500Hz, the bias voltage is 1800V, the filament current is 18A, and the high voltage used is 70kV; the vacuum electron beam scanning mode is under the surface scanning mode, the spot diameter is 200μm, the scanning speed is 800mm / min, and the electron beam current is 5mA.

[0148] That is, the difference between this embodiment and embodiment 2 is only that: in this embodiment, the scanning speed is different, which is 800 mm / min.

[0149] Comparative Example 1

[0150] This comparative example provides a method for preparing a CuZr shape memory amorphous composite material, comprising the following steps:

[0151] Step 1, Ingredients:

[0152] The surfaces of pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum are polished to remove the oxide layer, and each raw material is ultrasonically cleaned with acetone / water cleaning solution, and then dried and set aside;

[0153] According to Cu 46 Zr 46 The atomic ratio of Al8 is calculated and the corresponding masses of the above-treated pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum are weighed based on a total mass of 30 g for later use.

[0154] Step 2, preparing alloy ingots:

[0155] Using the arc melting method, the pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum weighed in step 1 were placed in a water-cooled crucible in the order of melting point from high to low in an arc furnace, and the vacuum was evacuated to 3.0×10 -4 After the pressure reaches 0.7 Pa, argon gas is filled in and the pressure reaches 0.7 atmospheres. Four arc melting treatments are performed under argon gas to obtain an alloy ingot.

[0156] The smelting current is 350A each time, and the smelting time is 80s each time.

[0157] Step 3, preparing alloy rods:

[0158] The alloy ingot obtained in step 2 was cut into blocks of 10 mm × 10 mm × 8 mm in size, placed in a suction casting copper mold, and melted under an argon atmosphere to obtain a molten liquid; the alloy liquid was sucked into a water-cooled copper mold and heated at 5 × 10 4 K / s cooling rate, and then rapidly solidified to obtain an amorphous alloy rod with a length of 6 cm and a diameter of 2.5 mm.

[0159] That is, the main difference between this comparative example and Example 1 is that no vacuum electron beam micro-area remelting treatment is performed, and suction casting is used for solidification and molding.

[0160] Comparative Example 2

[0161] This comparative example provides a method for preparing a CuZr shape memory amorphous composite material, comprising the following steps:

[0162] Step 1, Ingredients:

[0163] The surfaces of pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum are polished to remove the oxide layer, and each raw material is ultrasonically cleaned with acetone / water cleaning solution, and then dried and set aside;

[0164] According to (Cu 46 Zr 46 Al8) 98 The atomic ratio of Fe1Ta1 is calculated and the corresponding masses of pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum after the above treatment are weighed based on a total mass of 30g for use.

[0165] Step 2, preparing alloy ingots:

[0166] Using the arc melting method, the pure copper, pure zirconium, pure aluminum, pure iron, and pure tantalum weighed in step 1 were placed in a water-cooled crucible in the order of melting point from high to low in an arc furnace, and the vacuum was evacuated to 3.0×10 -4 After the pressure reaches 0.7 Pa, argon gas is filled in and the pressure reaches 0.7 atmospheres. Four arc melting treatments are performed under argon gas to obtain an alloy ingot.

[0167] The smelting current is 350A each time, and the smelting time is 80s each time.

[0168] Step 3, preparing alloy rods:

[0169] The alloy ingot obtained in step 2 was cut into blocks of 10 mm × 10 mm × 8 mm in size, placed in a suction casting copper mold, and melted under an argon atmosphere to obtain a molten liquid; the alloy liquid was sucked into a water-cooled copper mold and heated at 5 × 10 4 K / s cooling rate, and then rapidly solidified to obtain an amorphous alloy rod with a length of 6 cm and a diameter of 2.5 mm.

[0170] That is, the main difference between this comparative example and Example 2 is that no vacuum electron beam micro-area remelting treatment is performed, and suction casting is used for solidification and molding.

[0171] Comparative Example 3

[0172] This embodiment provides a method for preparing a CuZr shape memory amorphous composite material, comprising the following steps:

[0173] Step 1, Ingredients:

[0174] The surfaces of pure copper, pure zirconium and pure aluminum are polished to remove the oxide layer, and each raw material is ultrasonically cleaned with acetone / water cleaning solution, and then dried and set aside;

[0175] According to Cu 46 Zr 46 The atomic ratio of Al8 is calculated and the corresponding masses of pure copper, pure zirconium and pure aluminum after the above treatment are weighed based on a total mass of 30g for later use.

[0176] Step 2, preparing alloy ingots:

[0177] Using the arc melting method, the pure copper, pure zirconium and pure aluminum weighed in step 1 were placed in a water-cooled crucible in the order of melting point from high to low in an arc furnace, and the vacuum was evacuated to 3.0×10 -4 After the pressure reaches 0.7 Pa, argon gas is filled in and the pressure reaches 0.7 atmospheres. Four arc melting treatments are performed under argon gas to obtain an alloy ingot.

[0178] The smelting current is 350A each time, and the smelting time is 80s each time.

[0179] Step 3, preparing alloy plate:

[0180] The alloy ingot obtained in step 2 was cut into blocks of 10 mm × 10 mm × 8 mm in size, placed in a suction casting copper mold, melted in an argon atmosphere, and the molten liquid was sucked into a water-cooled copper mold by vacuum suction casting. 4 K / s cooling rate, and rapid solidification was achieved to obtain an amorphous alloy plate with a size of 2mm×8mm×50mm.

[0181] Step 4: vacuum electron beam micro-area remelting treatment:

[0182] The amorphous alloy plate obtained in step 3 is placed on a copper substrate with a size of 500 mm × 500 mm × 500 mm, and the vacuum degree of the vacuum electron beam micro-area remelting furnace chamber is ≤ 8 × 10 -3 Pa, the vacuum degree of the welding chamber is ≤9×10 -3Pa, and then, a vacuum electron beam micro-area remelting treatment is performed to sequentially form an ultra-thin surface melting layer and a heat-affected layer on the surface of the amorphous alloy plate to obtain an amorphous material with a sandwich structure, namely, the CuZr shape memory amorphous composite material.

[0183] Among them, the focusing current of the electron beam is 607.4mA, the scanning frequency is 500Hz, the bias voltage is 1800V, the filament current is 18A, and the high voltage used is 70kV; the vacuum electron beam scanning mode is under the surface scanning mode, the spot diameter is 200μm, the scanning speed is 1000mm / min, and the electron beam current size is 4.5mA.

[0184] That is, the main difference between this comparative example and Example 1 is that the beam current of the electron beam is different, which is 4.5 mA.

[0185] Experimental Section

[0186] (I) Microstructure analysis

[0187] The cast samples prepared in Example 1, Example 2, Example 5, Example 6, Example 7, Example 8 and Comparative Example 2 and Comparative Example 3 of the present invention were taken as examples, and their microstructures were tested respectively, and the test results are as follows: Figure 1-Figure 5 shown.

[0188] Figure 1 The Cu 2+ treated by vacuum electron beam surface scanning in Example 1 46 Zr 46 The microstructure of the Al8 cast sample shows that the Cu 46 Zr 46 In the Al8 cast sample, there is a B2 CuZr crystal region with shape memory in the heat affected zone (e.g. Figure 1 The darkest area in the middle) and the ultra-thin amorphous area on the surface (such as Figure 1 The lightest area in the upper middle section shows that the Cu 46 Zr 46 Al8 cast amorphous alloy can be successfully used to prepare CuZr shape memory amorphous composite materials, which shows that the method of the present invention can form sandwich composite structure materials in situ in amorphous alloys and couple the characteristics of amorphous alloys with those of crystal structures.

[0189] Figure 2 The (Cu) treated by vacuum electron beam surface scanning in Example 2, Example 5, Example 6 and Example 7 of the present invention 46 Zr 46 Al8) 98Microstructure picture of Fe1Ta1 alloy sample, where: Figure 2 (a) Figure 2 (b) Figure 2 (c) and Figure 2 (d) (Cu) of Example 2, Example 5, Example 6 and Example 7 respectively 46 Zr 46 Al8) 98 The microstructure image of the Fe1Ta1 alloy sample at a scale of 200 μm. The scanning speed of the samples of Examples 2, 5, 6 and 7 was maintained at 1000 mm / min, and the beam currents of the samples of Examples 2, 5, 6 and 7 were 5 mA, 5.5 mA, 6 mA and 7 mA respectively. Figure 2 (a) Figure 2 (b) Figure 2 (c) and Figure 2 The area marked by the double-headed arrows in (d) (also the darkest area in each figure) represents the corresponding (Cu 46 Zr 46 Al8) 98 Shape memory B2 CuZr crystal region in the heat affected zone of Fe1Ta1 as-cast sample.

[0190] By comparison Figure 2 (a) with Figure 1 It can be seen that after the introduction of doping elements Fe and Ta, the depth of the shape memory B2CuZr crystal area in the heat affected zone and the ultra-thin amorphous area on the surface increased, indicating that the introduction of Fe and Ta can change the Cu 46 Zr 46 Glass-forming ability and thermal stability of Al8 alloy.

[0191] And by comparison Figure 2 (a) Figure 2 (b) Figure 2 (c) and Figure 2 (d) It can be seen that as the beam size gradually increases from 5mA to 7mA, the depth of the shape memory B2 CuZr crystal area in the heat affected zone and the ultra-thin amorphous area on the surface gradually increases, and the crystal volume fraction is greatly increased. This shows that under the condition of keeping the scanning speed unchanged, increasing the beam size can greatly increase the energy input. Greater energy brings greater heat input, increases the penetration ability of the electron beam, slows down the heat dissipation rate, and obtains more crystal volume fraction and thicker sandwich structure.

[0192] Figure 3 This is a cross-sectional microscope image of the cast sample of Example 8. Figure 3In the figure, the lightest area (such as the top layer) is the ultra-thin amorphous area on the surface, the darkest area is the shape memory B2 CuZr crystal area in the heat-affected zone, and the area with moderate color depth is the cast amorphous alloy matrix.

[0193] And by comparison Figure 3 and Figure 2 (a) It can be seen that the depth of the shape memory B2 CuZr crystal region increases sharply as the scanning speed decreases while the beam size remains unchanged. This shows that reducing the scanning speed can increase the electron beam residence time per unit area while keeping the beam size unchanged, thereby greatly increasing the energy and bringing greater heat input, slowing down the heat dissipation rate, and obtaining more crystal volume fraction and thicker sandwich structure. Therefore, the amorphous composite structure can be effectively controlled by adjusting the beam size and scanning speed, and different crystal structures bring different mechanical properties.

[0194] Figure 4 For Comparative Example 2 (Cu 46 Zr 46 Al8) 98 Microstructure picture of Fe1Ta1 as-cast sample, Figure 4 (a) is the (Cu 46 Zr 46 Al8) 98 Microstructure picture of Fe1Ta1 as-cast sample at 400μm scale, Figure 4 (b) is the (Cu 46 Zr 46 Al8) 98 The microstructure of the Fe1Ta1 cast sample at 200μm scale. Figure 2 (a) It can be seen that the (Cu 46 Zr 46 Al8) 98 The Fe1Ta1 suction casting alloy has a typical amorphous structure, which shows that the alloy can still form an amorphous state in a wide temperature range after microalloying.

[0195] Figure 5 The Cu of Comparative Example 3 46 Zr 46 Microstructure picture of Al8 cast sample, and compared with Figure 1 It can be seen that when the electron beam current is reduced to 4.5 mA, the depth of the shape memory B2 CuZr crystal region in the heat affected zone and the ultra-thin amorphous region on the surface is significantly reduced, which is not conducive to the formation of the sandwich structure. Therefore, the electron beam current is preferably 5-7 mA.

[0196] (II) Mechanical properties test

[0197] The present invention also takes the cast samples prepared in Comparative Examples 1-3 and Examples 1-8 as examples, and tests the compressive mechanical properties thereof, and the test results are as follows: Figure 6 As shown. Among them, Figure 6 (a) is a graph showing the changes in the compressive mechanical properties of Comparative Example 1 and Comparative Example 2. Figure 6 (b) is a graph showing the changes in the compressive mechanical properties of Comparative Example 3 and Examples 1-4, Figure 6 (c) is a graph showing changes in the compressive mechanical properties of Example 2, Example 5, Example 6, Example 7 and Example 8.

[0198] And by Figure 6 (a) It can be seen that compared with Comparative Example 1, the Cu 46 Zr 46 The room temperature plasticity of Al8 amorphous alloy is significantly improved, which is due to the addition of positive mixing enthalpy elements Fe and Ta in Comparative Example 2 compared with Comparative Example 1. The addition of positive mixing enthalpy elements Fe and Ta can lead to phase separation. At the same time, the formation of a non-uniform structure in the amorphous phase leads to the activation of multiple shear bands, thereby improving the plasticity of the alloy.

[0199] Figure 6 (b) By comparing Example 1 and Comparative Example 3, it can be seen that for Cu 46 Zr 46 For Al8 samples, increasing the current can significantly improve the mechanical properties of the alloy; at the same time, after vacuum electron beam surface scanning treatment, compared with Cu 46 Zr 46 Compared with the Al8 sample, the compression plasticity after microalloying treatment is improved. By comparing Example 3, Example 4 with Example 1, it can be seen that although the compression plasticity of Example 3 and Example 4 is significantly improved, their plasticity is also significantly reduced, indicating that although adding Fe or Ta alone can also improve the Cu 46 Zr 46 By comparing Example 2 with Example 1, it can be seen that when Fe and Ta are introduced at the same time, Fe and Ta can work together to improve the plasticity to ≥10% while ensuring the compressive strength.

[0200] Figure 6In (c), by comparing Example 2, Example 5, Example 6, Example 7 and Example 8, it can be seen that as the beam size increases, the plasticity of the alloy is improved. Among them, the compressive strength of Example 6 and Example 7 even exceeds that of the amorphous alloy matrix. At the same time, it can be seen that as the scanning speed decreases, the plasticity of Example 8 increases to ~15%, and the compressive strength increases to ~2.2GPa. The plasticity and compressive strength of the sample are significantly improved, which is attributed to the formation of more crystal structures in the alloy.

[0201] In summary, in the preparation method of the present invention, microalloying has an important influence on the structure and properties of amorphous alloys. Adding positive mixing enthalpy Fe and Ta elements can effectively improve Cu 46 Zr 46 The room temperature plasticity of Al8 amorphous alloy and the heterogeneous structure produced in the form of strong medium-short ordered or amorphous phase separation are the main reasons for improving the plasticity of CuZrAl bulk amorphous alloy. 46 Zr 46 The plasticity of Al8 bulk cast amorphous alloy provides a promising approach.

[0202] In the preparation method of the present invention, the beam size also has an important influence on the microstructure and mechanical properties of the amorphous alloy. And it can be seen from the experimental results of the present invention that under a smaller beam size and a faster scanning speed, the energy input is limited, the strength of the amorphous composite material is reduced, and the compression plasticity is also small, which is difficult to achieve industrial application. With the increase of the beam size, the plasticity and strength of the amorphous composite material are greatly improved, which shows that while keeping the scanning speed unchanged, increasing the beam size can effectively increase the heat input and improve the mechanical properties of the amorphous composite material. And the scanning speed also has an important influence on the microstructure and mechanical properties of the amorphous alloy. And in the above-mentioned experimental results of the present invention, the plasticity and strength of Example 7 are improved, indicating that when the beam size is unchanged, reducing the scanning speed can improve the mechanical properties of the alloy. Therefore, by simultaneously regulating the beam size and the scanning speed, the organization and performance of the amorphous composite material can be effectively adjusted, and an amorphous composite material with the required target performance can be prepared according to actual use requirements.

[0203] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing a CuZr shape memory amorphous composite material, characterized in that: The following steps are involved: According to the alloy material (Cu x Zr y Al z ) 100-n M n According to the stoichiometric relationship, weigh the corresponding mass of each metal element raw material and set aside; Wherein, M is Fe and Ta in equal atomic ratio; n is the atomic percentage of the doping element M in the CuZr shape memory amorphous composite material, and n %=2%; x , y , z The alloy materials (Cu x Zr y Al z ) 100-n M n The atomic percentage of Cu, Zr and Al in the alloy is 44% or less x %≤48%,44%≤ y %≤48%,6%≤ z %≤8%, x + y + z =100; The weighed metal raw materials are placed in an electric arc furnace, evacuated and filled with argon gas, and arc melting is performed under argon gas to obtain alloy ingots; Melting the alloy ingot to form a molten liquid, placing the molten liquid in a mold, and cooling the molten liquid to obtain an amorphous alloy plate; Placing the amorphous alloy plate on a substrate, and performing a vacuum electron beam micro-area remelting treatment on the surface of the amorphous alloy plate to form a heat-affected layer and a surface ultra-thin melt layer on both the upper and lower surfaces of the amorphous alloy plate, thereby obtaining an amorphous material with a sandwich structure, namely, the CuZr shape memory amorphous composite material; The process parameters of the vacuum electron beam micro-area remelting treatment are: The vacuum degree of the furnace chamber is ≤8×10 -3 Pa, the vacuum degree of the welding chamber is ≤9×10 -3 Pa; The electron beam focusing current is 607~608mA, the scanning frequency is 500Hz, the bias voltage is 1800V, the filament current is 18A, and the high voltage used is 70kV; When the vacuum electron beam scanning mode is the surface scanning mode, the spot diameter is 200 μm, the scanning speed is 500-1200 mm / min, and the electron beam current is 1-8 mA. The arc melting process is performed at least three times; and each time the arc melting process is performed, the melting current is 300-400A, and the melting time is 60-90s.

2. The preparation method according to claim 1, characterized in that The interval between two adjacent arc melting treatments is 2 to 3 minutes.

3. The preparation method according to claim 1, characterized in that: When cooling the molten liquid, the mold used was a water-cooled copper mold, and the cooling rate was 5×10 4 K / s.

4. A CuZr shape memory amorphous composite material prepared by the preparation method according to any one of claims 1 to 3.

5. The CuZr shape memory amorphous composite material according to claim 4, characterized in that: The CuZr shape memory amorphous composite material comprises an upper surface layer, a middle layer, and a lower surface layer from top to bottom.

6. The CuZr shape memory amorphous composite material according to claim 5, characterized in that: The upper surface layer includes, from top to bottom, an upper surface ultra-thin zone and an upper heat-affected zone; Wherein, the upper surface ultra-thin area is an amorphous structure; The upper heat-affected zone is located between the surface ultra-thin zone and the middle layer, and the upper heat-affected zone is a shape memory type B2 crystal phase.

7. The CuZr shape memory amorphous composite material according to claim 5, characterized in that: The lower surface layer includes, from top to bottom, a lower heat-affected zone and a lower surface ultra-thin zone; Wherein, the lower heat-affected zone is located between the surface ultra-thin zone and the intermediate layer, and the lower heat-affected zone is a shape memory type B2 crystal phase; The lower surface ultra-thin area is an amorphous structure.

8. The CuZr shape memory amorphous composite material according to claim 5, characterized in that: The intermediate layer is an original amorphous structure.

Citation Information

Patent Citations

  • Copper-zirconium based amorphous alloy, and preparation method

    CN1958831A